Evaluation of the relationship between gastroptosis and reflux in pediatric patients - Tangul, Sevgi Ulusoy; Senayli, Atilla (Frontiers in Medicine, 2025)
PurposeGastroesophageal reflux (GER) is a common issue in childhood, characterized by the regurgitation of stomach contents into the esophagus. As a result, pain in the epigastric region, nausea, and vomiting may occur. Gastroptosis, on the other hand, is an anatomical anomaly defined by the downward displacement of the stomach into the pelvic region and is rarely reported in the literature. The overlapping symptoms of these two conditions suggest a potential relationship between them. This study aims to determine the relationship between patients diagnosed with GER and those found to have gastroptosis using contrast-enhanced esophagus, stomach, and duodenum X-ray [upper gastrointestinal (GI) series] among patients presenting to the Pediatric Surgery Clinic.MethodsThe study included 64 patients aged 1–18 years who presented with chronic epigastric region pain, nausea, and vomiting suggestive of GER. The patients were divided into two groups: those diagnosed with gastroptosis (n = 36) and a control group with normal stomach positioning (n = 28). Gastroptosis was classified into three grades based on stomach positioning, and gastroptosis and control groups were compared regarding sociodemographic data, findings from upper GI series, and pH monitoring results.ResultsThe median age of the study group was 14 years (3–18 years), and the majority of the patients were female (28/36). Patients with gastroptosis had significantly higher rates of alkaline reflux (p = 0.037). Although the frequency of alkaline reflux increased as the degree of gastroptosis increased, no significant difference was observed in the rates of acid reflux between the control and gastroptosis groups.ConclusionThe incidence of alkaline reflux is higher in children with gastroptosis. This suggests relationship between anatomic changes in the stomach and alkaline reflux. This study contributes to the literature as one of the first to demonstrate a connection between gastroptosis and alkaline reflux in pediatric patients, contributing to the literature. Considering the serious complications associated with alkaline reflux, such as Barrett’s esophagus and esophageal cancer, it is recommended that children with gastroptosis be managed with conservative treatment and closely monitored.